Determination of Helicobacter pylori Virulence by Simple Gene Analysis of the cag Pathogenicity Island - Ikenoue, Tsuneo (American Society for Microbiology, 2001)
Nucleic acid amplification was performed for five loci in the cag pathogenicity island (PAI) of Helicobacter pylori (comprising cagA, the cagA promoter region, cagE, cagT, and the left end of cagII [LEC]), and gastric inflammation in patients was evaluated. Of 204 H. pylori isolates from Japanese patients (53 with peptic ulcer, 55 with gastric cancer, and 96 with chronic gastritis), 197 (96.6%) were positive for all five loci. Two isolates (1%) were negative for all five loci, and five isolates (2.4%) were positive for only cagA and LEC. These latter seven isolates were all from patients with mild chronic gastritis. Neutrophil infiltration in gastric mucosa was significantly milder in patients infected with partially or totally deleted-PAI strains than in those with intact-PAI strains. The cagE gene was a more accurate marker of an intact cag PAI than the cagA gene, and cagE seemed to be more useful in discriminating between H. pylori strains causing different rates of disease progression.